Answer:
..................
Step-by-step explanation:
................................
Answer:
The right answer is C
Step-by-step explanation:
Answer: {y,x} = {4,2} ) ) ) )4
Step-by-step explanation: y
[2] y = -2x + 8
// Plug this in for variable y in equation [1]
[1] (-2x+8) - x = 2
[1] - 3x = -6
// Solve equation [1] for the variable x
[1] 3x = 6
[1] x = 2
// By now we know this much :
y = -2x+8
x = 2
// Use the x value to solve for y
y = -2(2)+8 = 4
Solution :
{y,x} = {4,2}
Answer:
c
Step-by-step explanation:
B*D?
B=-2
D=-6
B*D=(-2)*(-6)=12